Numerical Investigation of Fluid-Structure, Thermal Coupling for a Heated Slab (Advances in Systems Science and Applications, 2023)
This work focuses on a numerical analysis of fluid-structure thermal couplingin a heating slab. The latter consists of a rectangular cross-section duct located in theconcrete slab of a discredited habitat. We modeled the thermal transfers of fluid flow in thepipe. In fact, the Navier-Stokes equations that govern this flow have been solvednumerically. These equations were by an implicit method of finite differences. The systemsof algebraic equations thus obtained were solved by the algorithms of Gauss and Thomas.The equation of conduction in the concrete slab was solved using the same methodology asthat of flow. In this work, we based on an algorithm that interacts non stationary solidmedium with a fluid medium consisting of permanent a state by ensuring equal flows andtemperatures on the common interface between the two mediums at every moment. Thenumerical simulation of heat transfers and the thermal behavior of the heating slab wereanalyzed for various parameters influencing thermal diffusion. The results obtained showthat the numerical methodology adopted for the control of fluid-structure coupling isacceptable in comparison with the literature.